Preparation method of wide distribution chemical manganese dioxide with aluminum additive for lithium manganate
Patent Information
- Application Number
- CN202611367072.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-04
- Publication Date
- 2026-10-13
AI Technical Summary
另有涉及化学二氧化锰制备的相关技术,亦未解决粒度宽分布与铝均匀掺杂的协同调控问题
(1)类球形形貌,提高振实密度。通过铝系复合添加剂的调控作用,一步反应制得类球形化学二氧化锰二次颗粒,颗粒球形度高,有利于提高前驱体振实密度,进而提升锰酸锂正极材料的加工性能和体积能量密度。
Smart Images

Figure CN122897440A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of new energy material preparation technology, and more specifically, to a method for preparing broad-distribution chemical manganese dioxide using aluminum-based additives for lithium manganese oxide. Background Technology
[0002] Lithium manganese oxide (LiMn2O4) is considered one of the most promising cathode materials for lithium-ion batteries due to its abundant resources, low cost, environmental friendliness, and good safety. Chemical manganese dioxide (CMD) is an important manganese source for the preparation of lithium manganese oxide, and its physicochemical properties have a crucial impact on the product performance. Studies have shown that lithium manganese oxide prepared using CMD as the manganese source has superior initial discharge capacity and cycle performance compared to products prepared using electrolytic manganese dioxide (EMD).
[0003] However, existing technologies for preparing chemical manganese dioxide still have many shortcomings. Traditional methods (such as thermal decomposition of manganese carbonate, calcination, acid leaching, and oxidation) produce products with irregular morphology and poor sphericity of secondary particles, resulting in low tap density during subsequent preparation of lithium manganese oxide, which affects the electrode's processing performance and volumetric energy density. Furthermore, the particle size distribution of chemical manganese dioxide prepared by existing methods is relatively concentrated, which is not conducive to close packing between particles.
[0004] Aluminum doping is an effective way to improve the cycle performance of lithium manganese oxide. Appropriate aluminum doping can stabilize the spinel structure and suppress the Jahn-Teller effect, thereby improving cycle performance. However, current technologies mostly involve solid-phase doping during the preparation of lithium manganese oxide, making it difficult to achieve uniform distribution of the doping elements, leading to a decrease in conductivity and cycle performance. Furthermore, lithium manganese oxide materials suffer from severe capacity decay under certain conditions, limiting their application in the field of power batteries.
[0005] In the prior art, patent application CN102267727A discloses a method for preparing a high-taper spherical lithium manganese oxide precursor, which uses a controlled crystallization method to synthesize spherical or near-spherical manganese carbonate precursors. However, its particle size distribution is narrow, and it does not involve the direct preparation of chemical manganese dioxide or aluminum doping modification. Other related technologies involving the preparation of chemical manganese dioxide also fail to solve the problem of synergistic control of wide particle size distribution and uniform aluminum doping.
[0006] Therefore, there is an urgent need in this field for a chemical manganese dioxide preparation method that can simultaneously achieve spherical morphology, wide particle size distribution, and uniform aluminum doping. Summary of the Invention
[0007] In view of this, the present invention provides a method for preparing broad-distribution chemical manganese dioxide using aluminum-based additives for lithium manganese oxide, aiming to solve the above-mentioned problems.
[0008] On one hand, the present invention provides a method for preparing broadly distributed chemical manganese dioxide using aluminum-based additives for lithium manganese oxide, comprising the following steps: S1, Dissolve manganese sulfate in deionized water to prepare a manganese sulfate solution, wherein the concentration of the manganese sulfate solution is 115 g / L to 160 g / L; S2, a strong oxidizing agent is added to the manganese sulfate solution to initiate the reaction; S3, during the reaction process, an aluminum-based composite additive is added, wherein the aluminum-based composite additive is dissolved in an acid solution and the pH is adjusted to 5.0-7.0, and the Al content is 4.0 g / L-30 g / L; S4, during the reaction, an alkaline solution is added, and the pH of the reaction system is adjusted to 2.0–5.0 using the aluminum-based composite additive. The oxidation reaction is carried out at 50℃–85℃ until manganese sulfate is completely oxidized to manganese dioxide. The concentration of Mn in the reaction solution is then measured. 2+ Concentration determines the oxidation endpoint; when Mn 2+ When the concentration stabilizes and no longer decreases, it is considered that manganese sulfate has been completely oxidized to manganese dioxide. S5, after the oxidation reaction is complete, the system is aged for 3 hours, then filtered, and the reactants are washed and dried to obtain chemical manganese dioxide.
[0009] Furthermore, the strong oxidizing agent is sodium persulfate and / or hydrogen peroxide.
[0010] Furthermore, the aluminum-based composite additive uses either aluminum hydroxyaluminate or aluminum hydroxide as the aluminum source.
[0011] Furthermore, the acid solution is any one of hydrochloric acid, sulfuric acid, and nitric acid.
[0012] Furthermore, in S3, chemical manganese dioxide, with a mass of 0.45% to 1.05% of the manganese sulfate, is added as a seed crystal during the reaction.
[0013] Furthermore, the reaction seed crystal is γ-type chemical manganese dioxide.
[0014] Furthermore, in S5, the washing involves placing the reactants in deionized water and washing them at a temperature of 50°C to 70°C for 2 to 5 times.
[0015] On the other hand, the present invention also provides an aluminum-doped γ-type chemical manganese dioxide prepared by the above method; Furthermore, the aluminum-doped γ-type chemical manganese dioxide has a spherical morphology, a purity ≥96%, and a particle size distribution of D10 of 1.0μm to 2.5μm, D50 of 3.0μm to 5.0μm, and D90 of 6.0μm to 10.0μm.
[0016] The present invention also provides the application of the aluminum-doped γ-type chemical manganese dioxide as a precursor for lithium-ion cathode materials.
[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) Spherical morphology improves tap density. Through the regulation of aluminum-based composite additives, spherical chemical manganese dioxide secondary particles are prepared in one step. The high sphericity of the particles is beneficial to improving the tap density of the precursor, thereby improving the processing performance and volumetric energy density of lithium manganese oxide cathode material.
[0018] (2) Wide particle size distribution, optimized packing efficiency. By synergistically controlling the reaction temperature, pH, stirring rate, and additive dosage, a wide particle size distribution of chemical manganese dioxide is achieved. Particles of different sizes fill each other to form a dense packing, thereby improving the tap density. Data from the examples show that the chemical manganese dioxide prepared by this invention has a D10 of 1.978 μm, a D50 of 3.812 μm, a D90 of 7.534 μm, and a D99.99 of 22.715 μm, with a particle size distribution significantly wider than that of the comparative example.
[0019] (3) Uniform aluminum doping stabilizes the crystal structure. A wet doping method is used, introducing aluminum simultaneously during the oxidation reaction to ensure uniform mixing of aluminum with manganese salt in the liquid phase, achieving atomic-level uniform doping. Compared to traditional solid-phase doping, this avoids the decrease in conductivity and cycle performance caused by uneven distribution of dopant elements. Furthermore, the resulting chemical manganese dioxide is γ-crystalline, exhibiting high crystallinity and excellent conductivity.
[0020] (4) Excellent cycle performance. The lithium manganese oxide cathode material prepared by the chemical manganese dioxide of this invention has a capacity retention rate of ≥95% after 200 cycles at 25℃ and 1C rate, which is far superior to the 88.02% of the comparative example. It significantly improves the cycle stability of lithium manganese oxide and is suitable for application scenarios with high requirements for cycle life, such as power batteries. Attached Figure Description
[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0022] Figure 1 These are SEM images of the samples from Example 1 and Comparative Example 1 of the present invention. Figure 2 The X-ray diffraction pattern of aluminum-doped chemical manganese dioxide prepared in an embodiment of the present invention is shown below. Figure 3This is a particle size distribution curve of the samples from Example 1 and Comparative Example 1 of the present invention; Figure 4 This is an EDS-mapping surface scan distribution diagram of aluminum element in the sample of Example 1 of the present invention; Figure 5 The graph shows the comparison of the capacity retention rate of the half-cells after 200 cycles when the chemical manganese dioxide prepared in Example 1 and Comparative Example 1 of this invention were used as precursors to prepare lithium manganese oxide cathode materials. Detailed Implementation
[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0024] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0025] Example 1 This embodiment provides a method for preparing broad-distribution chemical manganese dioxide, an aluminum-based additive for lithium manganese oxide. The preparation method of this embodiment includes the following steps: (1) Preparation of manganese sulfate solution: Dissolve manganese sulfate in deionized water to prepare a 4500mL manganese sulfate solution with a concentration of 115g / L, and place it in a 20L fully automatic reactor.
[0026] (2) Add seed crystals: Add 2.3g of γ-type chemical manganese dioxide to the reaction vessel as seed crystals. The mass of the seed crystals is 0.45% of the mass of manganese sulfate.
[0027] (3) Set reaction conditions: Set the temperature of the reaction system to 50℃ and the stirring rod speed of the reactor to 200 rpm.
[0028] (4) Preparation of oxidant: Prepare 5L of sodium persulfate solution with a concentration of 164.8g / L as a strong oxidant, and add it to the reactor through a constant flow pump at a rate of 0.6mL / min.
[0029] (5) Preparation of aluminum-based composite additives: Using aluminum hydroxide as the aluminum source, add 37% concentrated hydrochloric acid until completely dissolved, dilute to volume with deionized water and adjust the pH to 6.0 to prepare an aluminum salt solution with an Al content of 4.0 g / L, and prepare a total of 1000 mL. Add to the reactor using a constant flow pump.
[0030] (6) Controlling the pH of the reaction: During the reaction, 100.8 g / L sodium hydroxide solution is added to the reaction vessel by a constant flow pump to adjust the pH of the reaction system to 2.0 to 5.0 in synergy with aluminum-based composite additives.
[0031] (7) Oxidation reaction: The oxidation reaction was carried out at 55℃ to oxidize manganese sulfate to manganese dioxide. During the oxidation reaction, samples were taken every 30 minutes to detect the Mn content in the reaction solution. 2+ Concentration, when Mn 2+ When the concentration stabilizes and no longer decreases, it is considered that divalent manganese ions have been completely oxidized to manganese dioxide. Mn 2+ Concentration can be detected by EDTA complexometric titration or inductively coupled plasma atomic emission spectrometry.
[0032] (8) Aging and washing: After the reaction is complete, allow the system to age for 3 hours, and then filter. Place the filtered filter cake in a deionized water solution with a mass of four times that of the filter cake, and wash for 30 minutes at 50°C and 150 rpm stirring speed, repeating the washing twice.
[0033] (9) Drying: Dry the washed product to obtain chemical manganese dioxide product.
[0034] The obtained chemical manganese dioxide exhibits a γ-type XRD pattern with high peak intensity and high crystallinity; its morphology consists of near-spherical secondary particles; the product's D50 is 3.81 μm. The particle size distribution results are shown in Table 1: D10 is 1.978 μm, D50 is 3.812 μm, D90 is 7.534 μm, and D99.99 is 22.715 μm.
[0035] The obtained chemical manganese dioxide and lithium carbonate were mixed in a stoichiometric ratio of Li:Mn=1.18:2, and then placed in a 5L inclined mixer for 120 min of mixing and grinding. The ground material was transferred to a crucible and placed in a muffle furnace for heating. The heating rate was set to 3℃ / min, and the material was calcined at 550℃ in air for 2 h, followed by calcination at 770℃ for 18 h. After natural cooling, LiMn2O4 cathode material was obtained.
[0036] LiMn₂O₄, acetylene black, and polyvinylidene fluoride were mixed evenly at a mass ratio of 0.90:0.05:0.05. 1 mL of N-methylpyrrolidone was added to prepare a slurry, which was then uniformly coated onto aluminum foil and dried in an oven at 105°C for 8 hours. The dried aluminum foil was cut into 14 mm diameter discs to serve as the positive electrode material. A 16 mm diameter Celgard 2400 polypropylene membrane disc was used as the separator, and a 16 mm diameter lithium metal disc was used as the negative electrode material. The electrolyte was 1.0 mol / L LiPF₆. A CR₂O₁₆ half-cell was assembled and charge-discharge tests were performed.
[0037] Example 2 (1) Preparation of manganese sulfate solution: Dissolve manganese sulfate in deionized water to prepare a 4500mL manganese sulfate solution with a concentration of 160g / L, and place it in a 20L fully automatic reactor.
[0038] (2) Add seed crystals: Add 7.6g of γ-type chemical manganese dioxide to the reaction vessel as seed crystals. The mass of the seed crystals is 1.05% of the mass of manganese sulfate.
[0039] (3) Set reaction conditions: Set the temperature of the reaction system to 85℃ and the stirring rod speed of the reactor to 150 rpm.
[0040] (4) Preparation of oxidant: Prepare 5L of hydrogen peroxide solution with a mass fraction of 3% as a strong oxidant, and add it to the reactor through a constant flow pump at a feeding rate of 0.6mL / min.
[0041] (5) Preparation of aluminum-based composite additives: Using aluminum hydroxide as the aluminum source, add 98% concentrated sulfuric acid until completely dissolved, dilute to volume with deionized water and adjust the pH to 6.0 to prepare an aluminum salt solution with an Al content of 30 g / L, and prepare a total of 1000 mL. Add to the reactor using a constant flow pump.
[0042] (6) Controlling the pH of the reaction: During the reaction, 100.8 g / L sodium hydroxide solution is added to the reaction vessel by a constant flow pump to adjust the pH of the reaction system to 2.0 to 5.0 in synergy with aluminum-based composite additives.
[0043] (7) Oxidation reaction: The oxidation reaction was carried out at 85℃ to oxidize manganese sulfate to manganese dioxide. During the oxidation reaction, samples were taken every 30 minutes to detect the Mn content in the reaction solution. 2+ Concentration, when Mn 2+ When the concentration stabilizes and no longer decreases, it is considered that divalent manganese ions have been completely oxidized to manganese dioxide. Mn 2+ Concentration can be detected by EDTA complexometric titration or inductively coupled plasma atomic emission spectrometry.
[0044] (8) Aging and washing: After the reaction is complete, allow the system to age for 3 hours, and then filter. Place the filtered filter cake in a deionized water solution with a mass of four times that of the filter cake, and wash for 30 minutes at 70°C and 150 rpm stirring speed, repeating the washing 5 times.
[0045] (9) Drying: Dry the washed product to obtain chemical manganese dioxide product.
[0046] The obtained chemical manganese dioxide product is γ-crystalline, nearly spherical, with a D50 of 3.1 μm. Lithium manganese oxide was prepared according to the method in Example 1, and a half-cell was assembled. The capacity retention rate was 95.1% after 200 cycles at 25°C and 1C.
[0047] Comparative Example 1 This comparative example provides a conventional method for preparing gamma-type chemical manganese dioxide (without adding aluminum-based composite additives).
[0048] Add 4500 mL of a 126.40 g / L manganese sulfate solution to a 20 L reactor, followed by 6.21 g of chemical MnO2 seed crystals. Set the temperature to 65 °C and the stirring speed to 200 rpm. Simultaneously add 1800 mL of a 151.75 g / L sodium permanganate solution at a rate of 0.8 mL / min, along with 1500 mL of a 151.4 g / L NaOH solution. Control the pH of the system to 2.36–2.56. Then, add the MnO2 seed crystals. 2+ The product is oxidized to MnO2. After the reaction is complete, the product is aged for 2 hours, filtered, and the filter cake is washed three times (15 min each time) with 5 times its weight of deionized water at 60℃ and 125 rpm. The product is then dried.
[0049] The tap density of the obtained γ-type chemical MnO2 was 2.38 g / cm³. 3 Mn 2+ The oxidation rate was 99.50%, and the XRD peak intensity was high. The particle size distribution results are shown in Table 1: D10 is 2.318 μm, D50 is 4.171 μm, D90 is 6.899 μm, and D99.99 is 14.793 μm.
[0050] The obtained chemical manganese dioxide and lithium carbonate were mixed in a stoichiometric ratio of Li:Mn = 1.18:2, and LiMn2O4 cathode material was prepared according to the same process as in Example 1, and CR2016 half-cells were assembled. Under the conditions of a test temperature of 25°C, a voltage range of 3–4.3V, and a 1C current rate, the reversible specific capacity of the material was 116.4 mAh / g, and the capacity retention rate was 88.02% after 200 charge-discharge cycles.
[0051] As can be seen from the above embodiments and comparative examples, the present invention, through the regulatory effect of aluminum-based composite additives, simultaneously introduces aluminum elements during the oxidation reaction, thereby achieving a near-spherical morphology, wide particle size distribution, and uniform aluminum doping of chemical manganese dioxide.
[0052] Specifically, such as Figure 1 The image shows a comparison of the SEM morphology of Example 1 and Comparative Example 1 of the present invention (accelerating voltage 15.0kV, working distance 7.5mm, magnification 5.00k, SE detector, scale bar: 10μm). The left image shows the chemical manganese dioxide prepared in Comparative Example 1, which has an irregular morphology and uneven particle dispersion. The right image shows the chemical manganese dioxide prepared in Example 1 of the present invention, which is a near-spherical secondary particle with high sphericity and smooth surface. This indicates that the addition of aluminum-based composite additives is beneficial to improving the morphology and dispersibility of the product.
[0053] like Figure 2 As shown, the XRD pattern of the chemical manganese dioxide prepared in Example 1 of this invention is in high agreement with the standard card of γ-type MnO2 (JCPDS No. 14-0644). The diffraction peaks are of high intensity and sharp shape, proving that the product is a pure γ-type crystal with excellent crystallinity. The phase purity is quantitatively detected by XRD Rietveld full spectrum fitting method according to GB / T 30904-2014 standard. The diffraction integral intensity of amorphous impurities and other manganese oxide impurities is subtracted from the JCPDS No. 14-0644 card, and the mass purity of the γ-type manganese dioxide phase is calculated to be ≥96%.
[0054] like Figure 3 As shown in Table 1, the particle size distribution of the chemical manganese dioxide prepared in Example 1 of this invention is significantly wider than that of Comparative Example 1. Wet particle size distribution data were obtained using a laser particle size analyzer. The dispersion medium was anhydrous ethanol, with a small amount of sodium hexametaphosphate added as a dispersant. After ultrasonic dispersion for 3 minutes, the particle size was measured using the laser, with the shading rate controlled at 10%-20%. Particle size and volume distribution data were collected according to the ISO 13320 particle size analysis standard. The particle size distribution was D10 = 1.978 μm, D50 = 3.812 μm, D90 = 7.534 μm, and D99.99 = 22.715 μm. In contrast, the particle size distribution of Comparative Example 1 was D10 = 2.318 μm, D50 = 4.171 μm, D90 = 6.899 μm, and D99.99 = 14.793 μm. This indicates that the present invention effectively broadens the particle size distribution range of chemical manganese dioxide through the regulation of aluminum-based composite additives, which is beneficial to improving the tap density of the precursor.
[0055] Table 1. Results of particle size index detection
[0056] like Figure 4 As shown, the total aluminum content was quantitatively determined using inductively coupled plasma optical emission spectrometry (ICP-OES); the aluminum element distribution was characterized using scanning electron microscopy with energy dispersive spectroscopy (EDS) at an accelerating voltage of 15 kV and a scanning resolution of 512 × 512. This invention, through the simultaneous dropwise addition of aluminum-based additives during the reaction process, resulted in a uniform and diffused distribution of aluminum elements throughout the entire manganese dioxide particle, without any obvious large-scale local enrichment. Uniform aluminum doping can form stable Al-O bonds in the subsequent lithium manganese oxide lattice, inhibiting manganese ion dissolution and fundamentally improving the cycle decay problem.
[0057] like Figure 5As shown, the half-cell assembly and electrode coating processes were performed according to GB / T 39864-2021 "Test Method for First Discharge Specific Capacity and First Charge-Discharge Efficiency of Lithium Manganese Oxide Electrochemical Performance". The charge-discharge tester used constant current charging and discharging, and the capacity retention rate was calculated using the formula: Capacity Retention Rate (%) = Nth Discharge Specific Capacity / First Discharge Specific Capacity × 100%. After 200 cycles at 25°C and 1C, the capacity retention rate of the lithium manganese oxide cathode material prepared from the chemical manganese dioxide obtained in Example 1 of this invention was 95.3%, while the capacity retention rate of the lithium manganese oxide cathode material prepared from the chemical manganese dioxide obtained in Comparative Example 1 was only 88.02%. The lithium manganese oxide prepared in Example 1 showed an approximately 7 percentage point improvement in cycle performance compared to the lithium manganese oxide prepared in the comparative example, indicating that the wide-distribution chemical manganese dioxide synthesized by the present invention through aluminum-based composite additives has significant advantages in the preparation of long-cycle lithium manganese oxide.
[0058] The above embodiments are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the present invention.
Claims
1. A method for preparing broad-distribution chemical manganese dioxide using aluminum-based additives for lithium manganese oxide, characterized in that, Includes the following steps: S1, Dissolve manganese sulfate in deionized water to prepare a manganese sulfate solution, wherein the concentration of the manganese sulfate solution is 115 g / L to 160 g / L; S2, a strong oxidizing agent is added to the manganese sulfate solution to initiate the reaction; S3, during the reaction process, an aluminum-based composite additive is added, wherein the aluminum-based composite additive is dissolved in an acid solution and the pH is adjusted to 5.0-7.0, and the Al content is 4.0 g / L-30 g / L; S4, during the reaction, an alkaline solution is added, and the pH of the reaction system is adjusted to 2.0–5.0 using the aluminum-based composite additive. The oxidation reaction is carried out at 50℃–85℃ until manganese sulfate is completely oxidized to manganese dioxide. The concentration of Mn in the reaction solution is then measured. 2+ Concentration determines the oxidation endpoint; when Mn 2+ When the concentration stabilizes and no longer decreases, it is considered that manganese sulfate has been completely oxidized to manganese dioxide. S5, after the oxidation reaction is complete, the system is aged for 3 hours, then filtered, and the reactants are washed and dried to obtain chemical manganese dioxide.
2. The method for preparing broad-distribution chemical manganese dioxide using aluminum-based additives for lithium manganese oxide according to claim 1, characterized in that, The strong oxidizing agent is sodium persulfate and / or hydrogen peroxide.
3. The method for preparing broadly distributed chemical manganese dioxide using aluminum-based additives for lithium manganese oxide according to claim 1, characterized in that, The aluminum-based composite additive uses either aluminum hydroxyaluminate or aluminum hydroxide as the aluminum source.
4. The method for preparing broad-distribution chemical manganese dioxide as an aluminum-based additive for lithium manganese oxide according to claim 1, characterized in that, The acid solution is any one of hydrochloric acid, sulfuric acid, or nitric acid.
5. The method for preparing broad-distribution chemical manganese dioxide as an aluminum-based additive for lithium manganese oxide according to claim 1, characterized in that, In S3, chemical manganese dioxide, with a mass of 0.45% to 1.05% of the manganese sulfate, is added as a seed crystal during the reaction.
6. The method for preparing broadly distributed chemical manganese dioxide as an aluminum-based additive for lithium manganese oxide according to claim 5, characterized in that, The seed crystals used in the reaction are γ-type chemical manganese dioxide.
7. The method for preparing broadly distributed chemical manganese dioxide using aluminum-based additives for lithium manganese oxide according to claim 1, characterized in that, In S5, the washing involves placing the reactants in deionized water and washing them at a temperature of 50℃ to 70℃ for 30 minutes, repeating the washing process 2 to 5 times.
8. An aluminum-doped γ-type chemical manganese dioxide prepared by the method for preparing a broad-distribution chemical manganese dioxide with aluminum-based additives for lithium manganese oxide as described in any one of claims 1 to 7.
9. The aluminum-doped γ-type chemical manganese dioxide according to claim 8, characterized in that, The aluminum-doped γ-type chemical manganese dioxide has a spherical morphology, a purity ≥96%, and a particle size distribution of D10 of 1.0μm to 2.5μm, D50 of 3.0μm to 5.0μm, and D90 of 6.0μm to 10.0μm.
10. The application of the aluminum-doped γ-type chemical manganese dioxide as described in claim 8 as a precursor for lithium-ion cathode materials.
Citation Information
Patent Citations
Preparation method of high-strength spherical lithium manganese oxide precursor
CN102267727A